Reducing burnout in call centers through HR practices - Castanheira, Filipa; Chambel, Maria José (Human Resource Management, 2010)
AbstractPrevious research on call centers has demonstrated that human resource (HR) practices can be related to employee stress; however, these studies did not examine the linking mechanisms underlying these associations. Using the job demands–control (JD‐C) model as a theoretical framework, we examine perceived job demands (namely, emotional dissonance and quantitative demands) and autonomy as potential mediators in the relationship between HR systems and burnout (exhaustion and cynicism). We distinguish between HR control systems, which include performance monitoring practices, and HR involvement systems, which include training, participation, and performance‐related pay. This study samples 811 employees working in 11 call centers. Our findings support the idea that HR systems can help reduce burnout in call centers by verifying that HR control systems associated with more emotional dissonance and less autonomy increase burnout. On the other hand, an HR involvement system decreases workers' burnout because it alleviates the job demands of emotional dissonance and quantitative demands. This study fills a gap in the literature between HR systems and burnout by demonstrating the role job demands and autonomy play in explaining how HR systems improve or decrease workers' exhaustion and cynicism. © 2010 Wiley Periodicals, Inc.